Conceptions on authentic assessment: What Indonesian EFL teachers conceive - Ayu Alif Nur Maharani Akbar; Gunadi Harry Sulistyo; Fika Megawati; Vina Virgianata Nuralisaputri (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2022)
In Indonesian context, as the 2013 Curriculum (K-13) has been introduced to EFL teachers to be implemented at schools, performance-based assessment starts to be applied at schools too, accompanying the curriculum implementation. This educational reform is meant to improve the quality of the teaching of English as a foreign language. However, little is known in the body of knowledge on EFL teachers’ challenges in implementing the authentic performance-based assessment in K-13 context, one of which, it was argued, is a facet that derives from EFL teachers’ conception on matters pertaining to authentic assessment. To address this, a survey was conducted to find out EFL teachers’ conceptions about authentic assessment, the role of feedback, and use of authentic assessment procedures in the context of such K-13 educational reform. A number of EFL teachers at lower and upper secondary levels of education in East Java across seniority were involved in the present survey. The findings of the study reveal among other things interesting phenomena where contradictions of conceptions were observed on authentic assessment. These findings have pedagogical implications that are educationally beneficial for the proper and successful implementation of authentic assessment under the 2013 curriculum – K-13.DOI: 10.26905/enjourme.v7i1.7018